Mean Platelet Volume Is a Poor Prognostic Factor in Patients Undergoing Liver Transplantation for Hepatocellular Carcinoma - Şentürk, Mustafa; İnce, Volkan and Üreyen, Orhan and Eyvaz, Kemal and Işık, Burak and Carr, Brian I and Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Mean platelet volume (MPV) reflects platelet activation. Platelets have an important role in tumor progression and metastasis. In this study, we wanted to investigate the effect of MPV on survival in patients undergoing liver transplantation (LT) for hepatocellular carcinoma (HCC). Materials and Methods: All data of 376 patients who underwent LT and pathologically diagnosed with HCC were analyzed. By determin ing the cut-off of MPV (10.2 fL), 2 groups with high and low MPV were formed. The groups were compared within themselves. Factors affecting survival were determined by univariate and multivariate analysis. Results: When the groups were compared, patients with low MPV had significantly higher platelet counts, larger tumor sizes, lower BMI, and higher recurrence rates. In multivariate analysis, GGT >104, AFP >200 μg/L, largest tumor diameter >5 cm, and lower MPV were found to be independent risk factors that affected the prognosis. Tumor-free survival was significantly worse in the lower MPV group (P = .002). Conclusion: Pre-transplant low MPV may be useful in predicting poor prognosis and a high rate of tumor recurrence in patients with HCC after liver transplantation. Cite this article as: Şentürk M, İnce V, Üreyen O, et al. Mean platelet volume is a poor prognostic factor in patients undergoing liver transplantation for hepatocellular carcinoma. Turk J Gastroenterol. 2025;36(3):169-173.